Effect of Tempering Temperature on Physical and Mechanical Properties of Martensitic Stainless Steel Repaired with Gtaw - Gangsar Pinilih; Kusmono Kusmono (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
One of the driving equipment to produce electricity that is widely used is gas turbines. To guarantee gas turbine can be operated according to its design and capacity, it is necessary to choose a material that is suitable for its operating conditions and working temperature. Commonly gas turbine compressor blade material is a martensitic stainless steel which has a high enough strength at the compressor working temperature. Damage that is often experienced occurs at the compressor blade and turbine blade. Gas tungsten arc welding (GTAW) build-up repair is one of the methods used to repair blades. This research was conducted to analyze the effect of tempering temperatures on martensitic stainless steel repaired with GTAW. Research was focus on mechanical properties and microstructure after repaired with GTAW and had heat treatment with various tempering temperatures. In the microstructure, all weld area of the specimens that were tempered at temperatures of 200, 500 and 600°C showed the same microstructure characteristics which consisted of a matrix of tempered martensite as well as chromium carbide. The size of tempered martensite at temperatures of 600°C is larger than 500 and 200°C. The strength and hardness of the material with a tempering temperature of 200°C is higher in value compared to tempering temperatures of 500°C and 600°C, while the toughness of the material with tempering temperature of 500°C is higher compared to 200°C and 600°C.